Comparison of 48‐week efficacy of tenofovir vs entecavir for patients with chronic hepatitis B: A network meta‐analysis. Issue 1 (22nd September 2020) - Con, Danny; Goodwin, Thomas; Majeed, Ammar; Roberts, Stuart; Kemp, William
Abstract: Both tenofovir disoproxil fumarate (TDF) and entecavir (ETV) are accepted as first‐line treatments for chronic hepatitis B (CHB). However, there are few randomized studies comparing their efficacy. The primary aim of this study was to compare the efficacy of TDF and ETV using a network meta‐analysis of randomized trials. The secondary aim was to additionally include propensity‐matched cohort studies in a conventional meta‐analysis. We systematically searched PubMed, EMBASE, Cochrane Library and Web of Science for published English‐language randomized and propensity‐matched studies between 1/1/2000 and 4/2/2020. Outcomes included undetectable HBV DNA, ALT normalization and HBeAg seroconversion at 48 weeks. We excluded patients who had co‐infection or significant prior treatment with antivirals. 13 517 participants from 16 studies (11 RCTs, n = 2675; five propensity‐matched cohort studies, n = 10 842) were included. Virological response at 48 weeks was higher in patients receiving TDF compared to ETV using both the network meta‐analytic approach (OR 1.69, P < .001) and the conventional meta‐analysis including propensity‐matched cohort studies (OR 1.40, P < .001). On subgroup analysis, this difference was only significant in HBeAg‐positive patients (OR 1.81, P = .037). There was limited evidence to suggest a higher rate of ALT normalization with ETV (OR 0.74, P = .07). There was no difference in rates of HBeAg seroconversion between the two antivirals. TDF is more likely than ETV to induce virological response at 48 weeks in treatment‐naïve CHB patients. Future studies should focus on elucidating associations between early and sustained virological response with adverse patient outcomes including development of HCC or cirrhosis.